2019
DOI: 10.1111/1759-7714.13270
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis identifies DUSP5 as a novel prognostic indicator for thyroid follicular carcinoma

Abstract: Background: Differentiated thyroid cancer involves thyroid follicular carcinoma (FTC) and papillary thyroid carcinoma (PTC). Patients with FTC have a worse prognosis than those with PTC for early metastasis through blood of FTC. However, the mechanism of poor prognosis of FTC is still unclear. Here, we aim to evaluate the role of DUSP5 in the prognostic evaluation of FTC. Method: We searched the Gene Expression Omnibus (GEO) database for the differentially expressed genes (DEGs) between FTC and PTC, and then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Downregulation of DUSP5 is associated with poor prognosis in several cancers. 50 , 55 , 56 Here, DUSP5 expression was lower in CADM1 + T cells, which increase during ATL disease progression, 24 , 41 than in CADM1 − T cells, regardless of ATL subtype ( Figure 3 C). Taken together, the results indicate that downregulation of DUSP5 in HTLV-1–infected cells contributes to ATL leukemogenesis and that restoring its expression by combination treatment with DNA demethylating agents and EZH inhibitors has anti-ATL effects.…”
Section: Discussionmentioning
confidence: 91%
“…Downregulation of DUSP5 is associated with poor prognosis in several cancers. 50 , 55 , 56 Here, DUSP5 expression was lower in CADM1 + T cells, which increase during ATL disease progression, 24 , 41 than in CADM1 − T cells, regardless of ATL subtype ( Figure 3 C). Taken together, the results indicate that downregulation of DUSP5 in HTLV-1–infected cells contributes to ATL leukemogenesis and that restoring its expression by combination treatment with DNA demethylating agents and EZH inhibitors has anti-ATL effects.…”
Section: Discussionmentioning
confidence: 91%
“…31 The protein encoded by DUSP5 is a member of the double specific protein phos- PARP inhibitors in the treatment of breast and ovarian cancer. 33 PCR results showed that MYC expression was activated in TPP treated groups. Cell migration related differential genes included PFN1, CKB, MICAL2, SCUBE3, and CXCL8.…”
Section: Discussionmentioning
confidence: 92%
“…However, the exact functions of the gene is not well defined. Recent data has shown that targeting DNPH1 makes BRCA ‐deficient cells sensitive to PARP inhibitors in the treatment of breast and ovarian cancer 33 . PCR results showed that MYC expression was activated in TPP treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…33 Low levels of DUSP5 in FTC are involved in proliferation, migration, and invasion, which further leads to poorer prognosis. Therefore, DUSP5 might serve as a novel therapeutic target for FTC, 34 it remains to be further researchers.…”
Section: Discussionmentioning
confidence: 99%